Regulatory fallacies in global telecommunications: The case of international mobile roaming - Günter Knieps; Patrick Zenhäusern (International Telecommunications Society (ITS), 2013)
International mobile roaming cartel agreements prompted the EU to intervene, firstly encompassing competition law measures by a cartel exemption, then initiating several competition proceedings based on the accusation of abuse of a dominant market position, and finally applying price regulations of increasing scope. The paper exposes the temporary market power regulations, including the designated local break out measures, as insufficient and misleading. The solution is to solve the cartel problem at its root, permitting visiting customers the freedom of choosing between their home operator and alternative carriers from the visited country by the implemention of carrier portability.
Keywords: K21; L51; L96; 330